Construction and accuracy analysis of a malnutrition prediction model for patients after proximal femoral nail anti rotation internal fixation - SHEN Lin; BAI Xiaojia; WANG Gang (陆军军医大学学报)
Objective‍　‍To explore the related factors of postoperative nutritional risk in elderly patients with proximal femoral nail anti rotation (PFNA) internal fixation and establish a prediction model of malnutrition. Methods‍　‍A total of 574 elderly patients who underwent PFNA internal fixation in the First Medical Center of Chinese PLA General Hospital from January 2021 to June 2024 were included and divided into malnutrition group (n=389) and good nutrition group (n=185). The differences in 39 indicators in aspects of physiological, psychological, social, economic, environmental and medical fields were compared between the 2 groups. Logistic analysis was used to screen the nutritional risk factors, and then a nomogram model was constructed based on these factors. Results‍　‍Advanced age, lower BMI, higher postoperative Self-Rating Anxiety Scale (SAS) score, less exercise before fracture, being farmers, higher economic pressure, lower preoperative albumin, preprotein and hemoglobin, and lower Barthel index before fracture were independent risk factors for nutritional risk in patients undergoing PFNA internal fixation (P<0.05). The nomogram prediction model based on the above factors had an AUC value of 0.995 (95%CI: 0.987~1.000) in predicting the risk of malnutrition in these patients. When the threshold probability >0.02, this model could be clinically beneficial in predicting the risk of postoperative malnutrition in patients after PFNA internal fixation. Conclusion‍　‍Our nutritional risk prediction model based on age, BMI, economic pressure, pre-fracture exercise and preoperative albumin and other indicators is constructed for the elderly patients after PFNA internal fixation, and the model has high accuracy and clinical application value.